Kajian Hukum Hak Cipta Penggunaan Audio Populer dalam Pembuatan Vidio - Andis Suci Aulia; Sukirno Sukirno (Faculty of Law, Diponegoro University, 2022)
This research aimz to knowing about copyright using a popular audio on making video. The research method used is sociological juridical, with descriptive analytical research specifications. The results of this study are violations of the use of popular audio in making videos using the dubsmash application in terms of the UUHC can be categorized as acts that include violations of economic rights in which the Creator or economic rights holders are taken away. The role of the Notary in legal protection of the creator in the case of the use of popular audio that makes videos using the Dubsmash application without permission from UUHC is as a consultant registered with the Directorate General. The obstacle is the binding of the creator of the Dubsmash application when uploading with the provisions of Mobile Motion and in the case of investigations carried out by PPNS based on an investigation warrant issued by officials who have competence in copyright.